Hemispheric Asymmetry in Visuotopic Posterior Parietal Cortex Emerges with Visual Short-Term Memory Load - Sheremata, Summer L. (Society for Neuroscience, 2010)
Visual short-term memory (VSTM) briefly maintains a limited sampling from the visual world. Activity in the intraparietal sulcus (IPS) tightly correlates with the number of items stored in VSTM. This activity may occur in or near to multiple distinct visuotopically mapped cortical areas that have been identified in IPS. To understand the topographic and spatial properties of VSTM, we investigated VSTM activity in visuotopic IPS regions using functional magnetic resonance imaging. VSTM drove areas IPS0–2, but largely spared IPS3–4. Under visual stimulation, these areas in both hemispheres code the contralateral visual hemifield. In contrast to the hemispheric symmetry observed with visual stimulation, an asymmetry emerged during VSTM with increasing memory load. The left hemisphere exhibited load-dependent activity only for contralateral memory items; right hemisphere activity reflected VSTM load regardless of visual-field location. Our findings demonstrate that VSTM induces a switch in spatial representation in right hemisphere IPS from contralateral to full-field coding. The load dependence of right hemisphere effects argues that memory-dependent and/or attention-dependent processes drive this change in spatial processing. This offers a novel means for investigating spatial-processing impairments in hemispatial neglect.